Antibiotic prophylaxis in obese patients submitted to bariatric surgery. A systematic review - Fischer,Maria Isabel (2014)
PURPOSE: To review the use of cefazolin in prophylaxis of surgical wound infection (SSI) in bariatric surgery (BS).METHODS: A systematic review was performed from October to November, 2013 using the following databases: The Cochrane Library, Medline, LILACS, and EMBASE. The inclusion criteria were randomized clinical trials and observational studies that were evaluated by two independent reviewers.RESULTS: Nine hundred and sixty one titles were recovered after preliminary analysis (title and abstract), seven studies remained for final analysis. There were three clinical trials (one with SSI, and two with antibiotic levels as the outcome), and four were observational studies (three cohorts and one case-control, all had SSI as the outcome). After administration of 1g or 2 g, levels of cefazolin in serum and tissue were suboptimal according to two studies. Results from observational studies indicated that different antibiotics were used for prophylaxis of SSI in BS and that use of other drugs may be associated with higher rates of SSI.CONCLUSION: The use of cefazolin for surgical wound infection prophylaxis in bariatric surgery is recommended, however further studies are needed in order to refine parameters as initial dose, redose, moment of administration and lasting of prophylaxis.